1997
DOI: 10.1103/physrevlett.78.2377
|View full text |Cite
|
Sign up to set email alerts
|

Internal Transport Barrier for Electrons in JT-60U Reversed Shear Discharges

Abstract: A new type of internal transport barrier (ITB) has been observed in JT-60U reversed shear discharges. It accompanies clear electron temperature and density pedestals and significant reduction of effective thermal diffusivities of electrons and ions (x eff e and x eff i ); x eff e sharply drops by a factor of 20 within 5 cm while x eff i is smaller than the conventional neoclassical value by a factor of 4 or more. The ratio of ion temperature to electron temperature was less than 1.5 inside the ITB. The ITB lie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 273 publications
(79 citation statements)
references
References 18 publications
0
79
0
Order By: Relevance
“…The reductions of the growth rate due to the negative magnetic shear and due to the nonzero k are confirmed, which are consistent with the internal transport barrier ͑ITB͒ formation observed in the large tokamaks with the negative magnetic shear and sheared rotation. [20][21][22] However, more elaborate investigation of the ITB formation is done by considering simultaneously several other effects, which are not included in this work, such as negative shear stabilization of the trapped-electron mode and stabilization of the ITG mode due to the Shafranov shift resulting from the increase of the safety factor in the core region for the negative shear case. 26 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reductions of the growth rate due to the negative magnetic shear and due to the nonzero k are confirmed, which are consistent with the internal transport barrier ͑ITB͒ formation observed in the large tokamaks with the negative magnetic shear and sheared rotation. [20][21][22] However, more elaborate investigation of the ITB formation is done by considering simultaneously several other effects, which are not included in this work, such as negative shear stabilization of the trapped-electron mode and stabilization of the ITG mode due to the Shafranov shift resulting from the increase of the safety factor in the core region for the negative shear case. 26 …”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] However, the results in these works only showed the dependence of positive growth rates on the magnetic shear. In Fig.…”
Section: Numerical Solution For Stable and Unstable Normal Modesmentioning
confidence: 98%
“…Some of the patterns are quite important for fusion application owing to its association with formation of transport barrier. Among new achievements of internal transport barriers in tokamaks, [29][30][31][32][33][34] the internal transport barrier for electron thermal energy is confirmed for the first time in the CHS as the toroidal helical plasmas. The internal transport barrier is associated with the bifurcation nature of the radial electric field.…”
Section: Introductionmentioning
confidence: 99%
“…the magnetic shearŝ. The effects of the latter on plasma microturbulence has been the subject of numerous experimental [19][20][21][22][23] , theoretical 24 , as well as numerical [25][26][27][28] studies. In this context, it was also found that negative magnetic shear can help improve the plasma confinement in a tokamak by decreasing the level of turbulence.…”
Section: B Robustness While Varying the Temperature Gradientmentioning
confidence: 99%